2012
DOI: 10.1007/s10499-012-9569-6
|View full text |Cite
|
Sign up to set email alerts
|

Amino acids composition and protein quality evaluation of marine species and meals for feed formulations in cephalopods

Abstract: Cerezo Valverde, J.; Martínez-Llorens, S.; Tomás Vidal, A.; Jover Cerda, M.; Rodriguez, C.; Estefanell, J.; Gairin, JI.... (2013). Amino acids composition and protein quality evaluation of marine species and meals for feed formulations in cephalopods. Aquaculture International. 21(2):413-433. doi:10.1007/s10499-012-9569-6. The amino acid composition and protein levels of three species of cephalopods 5 (Octopus vulgaris, Loligo gahi and Todarodes sagittatus), the natural diets of common 6 octopus (O. vulgaris) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(25 citation statements)
references
References 45 publications
1
22
0
Order By: Relevance
“…Octopus maya) and subtropical-temperate (O. mimus) octopuses. We also provide valuable insights on the effect of environmental conditions on the digestion and final use of nutrients by these 2 species , and presumably other species of octopods as well (Farías et al 2011, Este fanell et al 2012, Cerezo Valverde et al 2013). The process of digestion begins when the digestive tract is ready to receive a meal.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Octopus maya) and subtropical-temperate (O. mimus) octopuses. We also provide valuable insights on the effect of environmental conditions on the digestion and final use of nutrients by these 2 species , and presumably other species of octopods as well (Farías et al 2011, Este fanell et al 2012, Cerezo Valverde et al 2013). The process of digestion begins when the digestive tract is ready to receive a meal.…”
Section: Discussionmentioning
confidence: 91%
“…In studies examining the chemical composition of 33 marine species, Cerezo Valverde et al (2012Valverde et al ( , 2013 concluded that arginine (Arg) and leucine (Leu) were the limiting amino acids (AA) in most of the analyzed samples of O. vulgaris diet. Thus, the authors concluded that the inclusion of those AA in crustacean-based diets could benefit the culture of O. vulgaris.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, for the bivalve I. bicolor both mantle and viscera were analyzed. Viscera tend to show lower concentrations of N, since there is less protein and more substances that work as energy reserves, such as carbohydrate and lipid (Mathew et al, 1999;Arafa et al, 2012;Valverde et al, 2013). Taxonomic differences may also contribute to accentuate differences in the concentrations of nitrogen.…”
Section: Nitrogen and Phosphorusmentioning
confidence: 99%
“…However, Zlatanos et al (2006) estimated the crude protein of O. vulgaris by the use of the traditional N-Prot factor 6.25, which probably overestimated the actual protein content of the octopus (see the discussion on nitrogen-to-protein conversion factors). High concentrations of protein (63-81% dw) were also recorded by Valverde et al (2013) in different species of molluscs, including mussel, squid, and octopus, using the N-Prot factor 6.25. Studies regarding protein concentration in sea hares are concentrated on the ink composition (e.g., Bezerra et al, 2004), on the effects of their seaweed diet on growth and physiology (e.g., Barile et al, 2004), and more frequently on neurochemistry aspects of Aplysia, a model organism in neurosciences (e.g., Hansen et al, 2004).…”
Section: Proteinmentioning
confidence: 99%
See 1 more Smart Citation